Frequency-dependent changes in calcium cycling and contractile activation in SERCA2a transgenic mice - Hashimoto, Katsuji (2000)
Objective: This study was undertaken to investigate the mechanism of altered contractility in hearts from transgenic mice overexpressing the sarcoplasmic reticulum (SR) Ca²⁺ ATPase (SERCA2a). In particular, we sought to determine whether the reported increase in contractility is freqnency-dependent, as might be expected if attributable to changes in SR Ca²⁺ loading. Methods: Intracellular [Ca²⁺] and contractile force were measured at room temperature (22 °C) simultaneously in fura-2-loaded isometrically-contracting trabeculae dissected from the hearts of FVB/N control (n=6) or SERCA2a transgenic (n=6) mice. Results: SERCA transgenics exhibit a positive force-frequency relationship, but this was flat in age- and strain-matched controls. SERCA transgenics exhibit a sizable increase in calcium transient amplitude relative to controls, with a concomitant increase in force generation at higher frequencies of stimulation. Amplitudes of Ca²⁺ transients (transgenics: 1.56 ± 0.09 μmol/l, controls: 1.21 ± 0.14) and twitches (transgenics: 21.71 ± 0.91 mN/mm², controls: 13.74 ± 1.67) were significantly different at 2.0 Hz stimulation (P < 0.05). Conclusion: An increase in SERCA expression increases the ability of the sarcoplasmic reticulum to store calcium, such that more calcium is available to be released during each heartbeat at higher stimulation rates.